The Usage of ICT in Shariah: online marriage - Mamat , Arifin; Mohd Yusof, Nasura (Centre for Promoting Ideas, USA, 2013)
Information and Communication Technology (ICT) has witnessed a rapid development and made a significant impact on human relationship, particularly in developing new means of communication. This new means of technology provides a system for its users to communicate with each other regardless of time, place and distance. This development has also affected the way Muslim practices Islam, such as the aqd of marriage which is now being conducted through the internet via video conferencing. However, there is no special provision in the Islamic Family Law in any states in Malaysia. Since Islam is a complete yet simple religion that has always encouraged Muslims to perform good deeds and prevent them from any hardship in life, Muslims are permitted to do things that can bring benefit (maslahat) to them. Hence, this paper discusses how an online marriage can be an alternative to the Muslim communities in general, and Malaysia in particular.